Tingkat Pemahaman Peternak Sapi Perah Terhadap Kasus Penyakit Mulut dan Kuku Di Lembang Bandung Barat - Fiqhy Rahman Aldeyano; Ajat Sudrajat; Anastasia Mamilisti Susiati; Raden Febrianto (Fakultas Pertanian Universitas Majalengka, 2023)
The purpose of the study was to determine the level of understanding of dairy farmers towards cases of Mouth and Hoof Disease (FMD) which includes knowledge, attitudes, and performance of farmers. The research method used is the survey method. The samples used in this study were 50 dairy farmers in Lembang District, Bandung Barat Regency who had at least 3 years of farming experience. The collected data is tabulated and analyzed in a quantitative descriptive manner. The results showed that farmers' knowledge of FMD disease that does not understan and Lack of Understanding as much as 0%, quite understand 18%, understand 42% and understand very well 34% ,and perfect as much as 6%. The prevention attitude carried out by farmers shows Not Good as much as 8%, Less Good 20%, enough as much as 46%, good as much as 26%, and Very Good 0%. The performance of farmers in handling FMD disease is not interested 0%, lack of interest 6%, the same 10%, Interest 26%, very interested 50%, deepening interest 8,% and very deepening as much as 0%. It is concluded that, the level of understanding of dairy farmers which includes knowledge, prevention, and handling attitudes in Lembang District, Bandung Barat Regency is quite good.